Pelatihan dan Pendampingan Pengolahan Air Bersih Bagi Masyarakat Kampung Yobeh Distrik Sentani Kabupaten Jayapura - Suhartawan, Bambang; Suyatno, Suyatno; B. Alfons, Alfred; Abel, Andrea K.M.; Sroyer, Katherina (JURNAL PENGABDIAN PAPUA, 2025)
Yobeh Village is part of the Sentani district and has 3 RWs and 7 RTs with 173 heads of families and a total population of 692 people. Some of the people of RW2 Kampung Yobeh live on the coast of the island in the Sentani lake area, approximately 56 families with a population of approximately 246 people. The waters of Lake Sentani are the "center of life" for the people of Yobeh village who are on the coast. They use the lake water as a place to earn a living as fishermen, throw away household waste and use it to fulfill their needs for bathing, washing and toilets and even as raw drinking water. Preliminary research results show that the water quality of Lake Sentani is polluted and does not meet the requirements for clean water. The dominant contaminants are odor, color, TSS, detergent, total coliform and Escherichia coli. These pollutants have quite a negative impact on human health, especially children. The community service takes the theme "Clean Water Processing" through the application of filtration technology with 4 filtration tubes with filtration media adjusted to the type of pollutants in the lake water. Tube 1 contains biofoam media, tube 2 contains polypropylene media, tube 3 contains Granular Activated Carbon (GAC) media and tube 4 contains Chlorine, Taste, and Odor (CTO) media. Testing the quality of the filtration water shows very significant changes and meets the requirements for clean, hygienic water. To meet the need for clean, hygienic water for the people of RW2 Yobeh village, three units of equipment were made to be used by every RT. The aim of the service is for the community to understand the importance of clean water for life, have the skills to assemble and operate clean water processing equipment and be able to maintain the sustainable operation of clean water processing equipment so that the need for clean, hygienic water for the community can be met.